A residual stress dependent multiaxial fatigue life model of welded structures. Issue 2 (31st July 2017) - Liu, Z.C.; Jiang, C.; Li, B.C.; Wang, X.G.
Abstract: In this paper, the influence of the residual stress on the fatigue performance of a welded structure under multiaxial loading modes is studied. First, the local stress state at weld toe is modified via introduction of the residual stress, and a new fatigue life estimation model considering the effect of the residual stress is established by modifying our recently proposed critical plane method. Second, the basic theory and procedure of the finite element simulation on the calculation of the welding residual stress are presented. Finally, a numerical simulation of an aluminum alloy flange‐to‐tube welding process is conducted, and the calculated residual stress is verified with X‐ray diffraction measurement. Furthermore, the performance of the proposed fatigue life estimation model is verified by the experimental data obtained in the fatigue test under different loading modes. It confirms that the consideration of the residual stress is important, especially under the out‐of‐phase loading mode.